Pengaruh Fraud Diamond Terhadap Indikasi Kecurangan Laporan Keuangan - Dimas Bagus Prakoso; Wahyu Setiyorini (University of Merdeka Malang, 2021)
Fraud in financial statements is a problem that cannot be underestimated. From year to year, cases of fraud are always found. In this case, the role of the auditor profession is needed to detect the possibility of fraud as early as possible, so as to prevent fraud and possibly prolonged scandals. When there is a material misstatement in the financial statements, the information is irrelevant as a basis for decision making because the analysis is not based on actual information. This study aims to analyze the effect of pressure on indications of financial statement fraud, analyze the effect of opportunity on indications of financial statement fraud, analyze the effect of rationalization on indications of financial statement fraud and analyze the effect of capability on indications of report fraud. plantation companies listed on the Indonesia Stock Exchange. The sample in the study was 16 companies during the period 2015 to 2019. The analysis technique used logistic regression analysis. The results of the analysis show that pressure, which is proxied by ROA, has a significant effect on the indication of fraudulent company financial statements. The opportunity has a significant effect on the indication of fraud in the company's financial statements. Rationalization has no effect on indications of fraud in corporate financial statements. The capability has no effect on indications of fraudulent corporate financial statements.